Perbaikan Proses Pembuatan PDO untuk Mencegah Terjadinya Keterlambatan Pembayaran Upah Karyawan Menggunakan Metode Value Stream Mapping - M Hudori; . Arfadila (JURNAL CITRA WIDYA EDUKASI, 2019)
A palm oil plantation company often experiences late payment of wages. This happens because in the Operational Fund Request (PDO) creating process, which start from the input of document on the realization of work in the field up to the payment of wages, it does not run according to the specified time. The purpose of this research was to propose an improvement in the PDO creating process to prevent late payment of wages using the Value Stream Mapping (VSM) method. This research was conducted on February 20th – May 27th, 2017 at a palm oil plantation company in Central Sulawesi. Data processing is carried out by the step of using the value stream mapping principle. The result showed that the proposed improvement using value stream mapping (VSM) is to create a future state map which is a concept of improvement in the PDO creating process up to the payment of wages for harvesting employees by eliminating wastes in the current state map is a waiting/delay time.